Asymmetric information in external versus internal promotions - Mario Bossler; Philipp Grunau (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
Individuals have two possible channels through which to obtain a managerial position: external and internal promotions. Employing the revised German Employment Register, we compare external and internal promotions by using multinomial logit regressions while accounting for workplace heterogeneity. Individual characteristics are hypothesized to exert differential effects because of their observability within and across workplaces. We find that actual working hours are a more important source of information for internal versus external promotions. By contrast, formal vocational degrees and initial job task complexity, which are also externally observed, are a relatively more important signal for external promotions. Consistent with statistical discrimination, women and foreigners face a more pronounced disadvantage in external promotions. For women, this differential effect is fully driven by promotions to executive positions characterized by high task complexity. Moreover, actual working hours show a strong positive interaction effect on women's prospects of promotion. – – Für Beschäftigte existieren zwei Kanäle um eine Führungsposition zu erreichen: die externe und die interne Beförderung. Anhand der neuaufgelegten deutschen Beschäftigtenstatistik vergleichen wir externe und interne Beförderungen mithilfe eines multinomialen Logit- Modells und unter Kontrolle für die Heterogenität zwischen Arbeitgebern. Wir nehmen an, dass die Charakteristika von Beschäftigten abhängig von ihrer Sichtbarkeit innerhalb von Betrieben und über Betriebe hinweg abweichende Einflüsse ausüben. Wir zeigen, dass die Realarbeitszeit für interne Beförderungen eine bedeutsamere Informationsquelle darstellt als für externe. Demgegenüber spielen formale Ausbildungsabschlüsse und die ursprüngliche Aufgabenkomplexität, welche beide auch über Betriebe hinweg sichtbar sind, eine größere Rolle bei externen Beförderungen. Übereinstimmend mit dem Konzept statistischer Diskriminierung unterliegen Frauen und Ausländer bei externen Beförderungen einem stärker ausgeprägten Nachteil. Bei Frauen ist dieses Ergebnis vollständig auf Beförderungen zu Managern bzw. leitenden Angestellten zurückzuführen, welche durch hohe Aufgabenkomplexität gekennzeichnet sind. Darüber hinaus zeigt die Realarbeitszeit einen starken positiven Interaktionseffekt auf die Beförderungsaussichten von Frauen.
Keywords: J41; J70; M12; M51; 330; promotions; asymmetric information; signaling; statistical discrimination